Selbstinszenierungen, Reputationskarrieren und Tricks frühneuzeitlicher Magier: eine Hinführung in Beispielen - Bulang, Tobias; Reich, Philip; Furrer, Paula (Daphnis, 2025)
Abstract Several historical examples illustrate the self-fashioning of the early modern magus in the era of book printing. Together, they outline a new type that appeared throughout Europe. The unorthodox methods used to build careers, generate public interest, and earn income were highly risky and uncertain. The early modern magus is a precarious and ambivalent figure. This conference volume presents him as an object of comparative studies.
Gesehen am 01.09.2025
Keywords: Geschichte 1450-1650; Selbstdarstellung; Magier